The impact of bariatric surgery on quality of life: a systematic review and meta‐analysis. Issue 8 (11th June 2015) - Lindekilde, N.; Gladstone, B. P.; Lübeck, M.; Nielsen, J.; Clausen, L.; Vach, W.; Jones, A.
Summary This study aims to review the obesity literature in order to assess the impact of bariatric surgery on quality of life and the between‐study variation by examining the standardized mean magnitude of effect in change in the levels of quality of life. The following databases EMBASE, PubMed, PsycINFO, CINAHL, the Cochrane Library and Web of Science were systematically searched for studies examining change in quality of life in adults receiving bariatric surgery for obesity. Seventy‐two studies were included with a total of 9, 433 participants treated for obesity with bariatric surgery. The average impact of bariatric surgery on quality of life corresponded to an effect size of 0.88 (95% CI: 0.80–0.96), indicating that bariatric surgery has a significant positive influence on quality of life in general. The impact varied considerably across studies with bariatric surgery showing a significantly greater positive influence on physical quality of life compared to mental quality of life. Bariatric surgery is effective in improving quality of life, especially when looking at physical well‐being. Greater focus on the psychological well‐being of the person undergoing surgery for obesity may lead to a better post‐surgery prognosis for more people.